The profile of contemporary ethnonational policy in the Republic of Altai - Persidskaia, Olga A.; Madiukova, Svetlana A. (The New Research of Tuva, 2016)
The article defines the regional model of contemporary ethnonational policy in the Republic of Altai (RA), taking into account both the regional details of ethnosocial processes and the particularities of the ethnic policy pursued by the authorities. The model includes structural and procedural components. Structural elements of the model are the legislative and executive institutions of power, public and kinship organizations. One of the priorities for the authorities of RA is to preserve the region’s status by strengthening the unity of the Altaians. At the same time, they are striving to preserve the status of indigenous peoples of the North granted to some sub-groups of the Altaians. Federal legislation provides material support to these groups. Among the key priorities of the regional powers are harmonizing interethnic relations, preserving traditional cultures and ethnocultural diversity in the Republic of Altai, language policy, coordinating culture and entertainment, controlling museums and promoting ethnic sports. Another part of the structural element includes civil self-government implemented via three types of public institutions, each with its own interests – consolidating Altaians as a single ethnicity, protecting the interests of small indigenous peoples (sub-ethnicities of the Altaians) and the revival of kinship organization of the zaysanat. The procedural model of ethnonational policy in its dynamic unfolding rests upon the foundations of the regional society: multi-ethnicity of Altai’s population, the special status of a republic within Russia, the presence of indigenous communities on its territory and the tourist appeal of the region. In the article, we provide an assessment of how efficient the ethnonational policy is in RA. Based on both expert survey and mass opinion poll we conducted in RA in 2013-2014, our study led us to a conclusion that in RA it is not implemented consistently or efficiently enough. The declared capabilities of ethnopolitical development of all peoples of the regions are not always implemented in the same way. As experts believe, the model of ethnonational policy implemented in RA is characterized by the rise of regional patriotism, while preserving the ethnic and cultural differences and providing selective support to some ethnic groups.